PENERAPAN TEKNOLOGI WEB DALAM SISTEM PEMESANAN MAKANAN (FOOD ORDER SYSTEM) SISTEMATIC LITERATUR REVIEW - Abel Abel; Andi Suciana Ahkas; Nur Aziza; Rika Wulan Dari; Mutmainnah Mutmainnah; Dhimas Tribuana (Jurnal Teknologi dan Bisnis Cerdas, 2025)
The implementation of web technologies in food ordering systems has experienced rapid growth in recent years, driven by post-pandemic digital transformation, increasing internet usage, and the adoption of mobile devices. This study aims to conduct a Systematic Literature Review (SLR) to identify technological trends, innovations, and implementation challenges of web-based food ordering systems during the 2020–2025 period. Referring to the PRISMA 2020 guidelines, 20 scientific articles were selected from an initial set of 100 articles sourced from Scopus and Google Scholar. The findings reveal five main points: (1) digitalization of ordering systems can increase operational efficiency by up to 45%; (2) QR Code integration supports accessibility without requiring application installation; (3) the use of RESTful API architecture enables real-time connectivity between customer, kitchen, and cashier modules; (4) the adoption of payment gateways such as QRIS, Midtrans, and Xendit enhances transaction security; and (5) the utilization of artificial intelligence (AI) supports personalized menus and automated recommendations. Additionally, the study highlights several critical success factors, including data security through SSL/TLS encryption, cloud-based scalability, responsive interfaces using modern frameworks, and appropriate selection of development methodologies. Future research is recommended to explore digital inclusion, the social impacts on labor, and implementation strategies for MSMEs with limited technological and financial resources.